Firm heterogeneity and the impact of payroll taxes - Anikó Bíró; Réka Branyiczki; Attila Lindner; Lili Márk; Daniel Prinz (Institute for Fiscal Studies (IFS), 2022)
We study the impact of a large payroll tax cut for older workers in Hungary. Motivated by the predictions of a standard equilibrium job search model, we examine the heterogeneous impact of the policy. Employment increases most at low-productivity firms offering low-wage jobs, which tend to hire from unemployment, while the effects are more muted for high-productivity firms offering high-wage jobs. At the same time, wages only increase at high-productivity firms. These results point to important heterogeneity in the incidence of payroll tax cuts across firms and highlight that payroll taxes have a significant impact on the composition of jobs in the labor market.
Keywords: H24; H32; J23; J31; 330; payroll tax; tax incidence; firm heterogeneity